Apprenticeship of Observation and Language Teacher Education: Insights and Implications for Future Teaching Practices - Bekleyen, Nilüfer (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study explores the perceptions of language-teacher candidates regarding their own English-language learning experiences during primary school, and how they intend to utilize these insights to enhance their instructional practices. Grounded in Lortie's (1975) concept of the apprenticeship of observation, which highlights how teachers’ beliefs are shaped by their own experiences as students, this study aims to elucidate how these past student experiences influence their future teaching strategies. The sample comprised 54 English-teacher candidates from southeastern Türkiye, all of whom attended public primary schools. All of the participants were Turkish native speakers or bilingual in Turkish and English, with an average of 13 years of English-language learning experience and a B2 proficiency level in the Common European Framework of Reference for Languages (CEFR). Data were collected through a Likert-type survey and semi-structured interviews. The survey provided quantitative insights, analyzed using descriptive statistics, while the interviews contributed qualitative data, which were analyzed thematically. Findings revealed that the teacher candidates were critical of their past language education, particularly because it relied on traditional, grammar-focused instruction with limited communicative activities. They advocated for a balanced approach to language skills, incorporating interactive and age-appropriate activities. The candidates emphasized the need for updated resources and continuous professional development, though perspectives varied on whether these should be institutional responsibilities or personal initiatives. Additionally, they highlighted effective classroom management and student engagement as essential components of successful language teaching. This study underlines future English teachers' varied perspectives and aspirations, as they draw upon their own learning experiences to refine their professional development and teaching effectiveness.